Kharkiv in the Period of Interpower: Maintenance of Law in the City at the End of 1918 - Потоцький, В’ячеслав (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article deals with the situation in the city of Kharkiv at the end of 1918. At this time, Ukraine was experiencing the completion of one more historical stage, preparing for new, more turbulent and tragic events. German troops which have been the guarantors of security of the state over the past ten months were evacuated from its territory, a popular uprising broke out against the hetman Pavlo Skoropadsky, the republican authorities that recognized the Directory were forming slowly, local Bolsheviks and other left-wing groups were getting noticeably more active. In December 1918 all these forces were represented in the provincial Kharkiv. Some of them, for example, the German command and the hetman’s guard, tried to transfer power to their successors in an organized manner. Others, on the contrary, tried to get to the controls as soon as possible. This multi-power lasted about a month, which became a real ordeal for the inhabitants of the city. Kharkovites tried to figure out a kaleidoscope of political developments, a variety of orders and decrees, the intricacies of official information and street rumors. Meanwhile, the criminal situation became more and more threatening: gangs of looters raged in rural districts, and shots were fired more often in Kharkiv itself. In the second half of December, the number of the city shops robberies became impressive. At that time, several influential forces were engaged in law enforcement: the German commandant’s office, the hetman’s guard, Directory fighters and socialist squads. However, all their efforts did not give the desired result, and ordinary Kharkovites were forced to organize self-defense units to protect their own homes. The culmination of anarchy in the city was the Bolshevik uprising on January 1–2, 1919, as a result of which Kharkiv was captured by armed units of the Red Army.